Penguatan Nilai Kebangsaan dalam Upacara Hormat Bendera Merah Putih: Reaktualisasi Konsep Kebangsaan Berbasis Maslahah - Muhammad Solikhudin (INSTITUT AGAMA ISLAM BANI FATTAH (IAIBAFA), 2022)
This article seeks to explain the strengthening of national values in the red and white flag honoring ceremony: the re-actualization of the concept of nationality based on maslahah. The purpose of the flag salute ceremony is to strengthen love for the Unitary State of the Republic of Indonesia and realize the common benefit of living together in a pluralistic and multicultural nation-state. Therefore, it is necessary to re-actualize the concept of nationality, especially with regard to respect for the flag based on maslahah. Furthermore, the concept of nationality in the view of Islam is compatible and does not need to be contradicted. Regarding the pros and cons of information on the article competition respecting the flag in the view of Islamic law, this must be addressed wisely and actually this competition is organized by BPIP in commemoration of santri day, so the right theme is about Islam and nationality. Respect for the flag is the nation's way of showing respect for the symbol of the State of Indonesia and love for the homeland. Regarding the respect for the flag which is reviewed with maslahah, then this is included in the realm of maslahah mursalah because there is no clear explanation in the scriptures or Hadith and this practice is included in the realm of daruriyat which was originally only the needs of religious people and the state. as well as being a nation on a secondary basis, but by implementing it, national unity and integrity will emerge, this shifts from ha>jiyat to daruriyat. Kata Kunci: Kebangsaan, Hormat Merah Putih dan Maslahah. Abstract: This article seeks to explain the strengthening of national values in the red and white flag honoring ceremony: the re-actualization of the concept of nationality based on maslahah. The purpose of the flag salute ceremony is to strengthen love for the Unitary State of the Republic of Indonesia and realize the common benefit of living together in a pluralistic and multicultural nation-state. Therefore, it is necessary to re-actualize the concept of nationality, especially with regard to respect for the flag based on maslahah. Furthermore, the concept of nationality in the view of Islam is compatible and does not need to be contradicted. Regarding the pros and cons of information on the article competition respecting the flag in the view of Islamic law, this must be addressed wisely and actually this competition is organized by BPIP in commemoration of santri day, so the right theme is about Islam and nationality. Respect for the flag is the nation's way of showing respect for the symbol of the State of Indonesia and love for the homeland. Regarding the respect for the flag which is reviewed with maslahah, then this is included in the realm of maslahah mursalah because there is no clear explanation in the scriptures or Hadith and this practice is included in the realm of daruriyat which was originally only the needs of religious people and the state. as well as being a nation on a secondary basis, but by implementing it, national unity and integrity will emerge, this shifts from hajiyat to daruriyat. Keywords: Nationality, Respect for Red and White and Maslahah.